The ends of history in the 21st century - Barros, Carlos (2019)
Having overcome the debate on the «end of history», whose post-1989 continuity is beyond doubt, we are with the new century in the debate on the «ends of history». We understand «ends» as the objectives that at the beginning of the 21st century are practically shaping the new and old social, economic and political subjects in the global sphere. We have identified five purposes in progress: Global Market, Islamic Caliphate, Socialism of the 21st century, Authoritarianism of the State and Democratic World Government, which we analyze in detail applying the past / present / future historiographical criterion (Immediate History).